Vitamin K2 can suppress the expression of Toll-like receptor 2 (TLR2) and TLR4, and inhibit calcification of aortic intima in ApoE-/- mice as well as smooth muscle cells. (February 2018) - Wang, Zhaojun; Wang, Zhongqun; Zhu, Jie; Long, Xinguang; Yan, Jinchuan
Background and objectives: Vascular calcification is a common complication in atherosclerosis. Accumulating evidence showed that Toll-like receptors (TLRs) mediate pro-inflammatory and atherosclerosis. Recent studies demonstrated that vascular calcification is one of the detrimental effects of vitamin K (Vit K) antagonists. However, the effects of Vit K on the expression of TLR2 and 4 and intimal calcification in artery remained unidentified. Methods and results: Eighteen ApoE -/- mice were randomly divided into model group, Vit K-treated group, and control group. The mice of model and Vit K-treated group were fed with high-fat diet, while control group mice were fed with normal diet. Mice of Vit K-treated group were administered orally with vitamin K2 (40 mg.kg −1 .day −1 ) for 12 weeks. Twelve weeks later the aortic sections of mice were acquired and stained with hematoxylin and eosin and von Kossa, respectively. Calcium content and activity of alkaline phosphatase (ALP) at aortic tissues were measured. The expression levels of TLR2 and TLR4 in aorta sections were detected by immunohistochemisty and RT-PCR, respectively. The effects of Vit K on cellular calcification were further studied in A7r5 SMCs. Results demonstrated that high-fat diet induced typical atherosclerosis with intimal calcification in ApoE -/- mice, while in Vit K-treated group atherosclerosis and calcium deposits were not serious; Vit K2 also inhibited cellular calcification in A7r5 SMCs. Quantitative analysis showed that calcium and ALP activity at aortic tissues in the Vit K-treated mice were significantly lower than that of the model group ( P  < 0.01); Compared to the control group, the expression levels of TLR2 and TLR4 in the model group were significantly higher ( P  < 0.05), while in Vit K-treated group the levels of TLR2 and 4 were significantly lower than that in the model group. Furthermore, the content of calcium was positively related to the expression levels of TLR2 and TLR4 mRNA at aortic tissues ( r  = 0.77 and r  = 0.79, respectively, both P  < 0.001). Conclusion: VitK2 can inhibit intimal calcification of aortic artery induced by high-fat diet in ApoE -/- mice and A7r5 SMCs calcification induced by β-sodium glycerophosphate, and meanwhile can reduce the expression of TLR2 and TLR4. These results suggested that the effects of VitK2 on vascular calcification may be associated with the expression of TLR2 and TLR4.